Analysis of The Interrelationship Between Minimum Wage Policy, Citizenship Status and Distribution of Labor Income in Indonesia Real Sector Industries - Kamar, Karnawi; Kusnadi, Iwan Henri; Indriastiningsih, Erna; Sihombing, Dina Agnesia; Indriani, Lely (Malikussaleh University, Aceh, Indonesia, 2024)
This study aims to analyze the wage gap between natives and immigrants currently working in the real sector in Indonesia. This study uses survey data with a sample of individuals aged between 20 and 55 years. This study uses a quantitative approach, utilizing segmentation analysis techniques. The conclusion of the study shows that immigrants earn higher average wages than natives, this difference is caused by several factors that can be directly identified such as education level, worker bargaining power and the capacity or skills possessed by the workforce. This gap is more pronounced in the middle of the income spectrum, where factors such as discrimination that generally occur in other countries do not occur in Indonesia and immigrant skills are considered better than local citizens. Companies in Indonesia generally still view foreign citizens working in Indonesia as having above average abilities. The suggestion from the study is that it is necessary to review the regulations governing wage policies and improve the protection of workers' rights, especially at the middle-income level, to address this gap. Policies should be focused on increasing local citizens' access to quality jobs, reducing informality in the labor market, and the government should provide active and proactive permission to develop the quality of local human resources by building education and training systems and facilities. This approach aims to create a more qualified and competitive local labor market.